A Bibliometric Analysis and Systematic Literature Review of Inquiry-Based Learning: Trends, Contributions, and Future Directions - Kurniawan Arizona; Joni Rokhmat; Agus Ramdani; Gunawan Gunawan; Aa Sukarso; Ramdhani Sucilestari (Jurnal Pendidikan Sains Universitas Muhammadiyah Semarang, 2026)
Inquiry-based learning (IBL) has become a widely recognized pedagogical approach that enhances student engagement through critical thinking, problem-solving, and hands-on exploration. This study conducted a bibliometric analysis and systematic literature review (SLR) of IBL research, using data from the Scopus database, covering articles published from 2001 to 2025. The analysis identified a significant increase in IBL publications starting in 2008, with a peak in 2020, reflecting growing global interest. The findings revealed that the United States and Indonesia were the top contributors, with substantial participation from countries like the United Kingdom, Germany, and China. Key institutions and authors played an important role in advancing IBL research, and interdisciplinary applications of IBL were observed beyond the social sciences. The study concluded by recommending further research to address the challenges in IBL implementation, enhance teacher training, and promote global collaboration, thus ensuring its continued development and impact in educational systems worldwide.